PROTECTIVE COATINGS FOR WALLS AND ROOF OF TANKS MADE OF GRANULAR FUSED NON-COMBUSTIBLE SUBSTANCES AGAINST FIRE EXTENSION - А. А. Aleksandrov; A. G. Gumerov; P. S. Khafizov; G. A. Sharipov (Aubakirov); Waldemar Kozlowski (Scientific Journal of Pedagogy and Economics, 2019)
As a result of the research, there has been improved the technology of applying new foaming agents and means of limiting the spread of the flame during fires in storage facilities. The analysis of putting out flammable liquids indicates that if the fire is not eliminated at the initial stage, the fire passes to a prolonged stage, where an additional amount of forces and means will be required. To eliminate this stage, an additional amount of forces and means will be required. There have been developed and experimentally tested protective coatings for the walls and roofs of tanks made of granular fusible non-combustible substances as additional passive protection against fire extension. Besides, in laboratory and semi-industrial conditions, there were studied the possibilities of using internal and external coatings. Protective coatings possess fire-resistant properties. They allow reducing the temperature of the walls of vertical steel tanks. The given protective coatings prevent the occurrence of static electricity charges.